Application of the build, operate, transfer (BOT) contract as a means of financing development of Waqf Land: Malaysian experience - Mohd Noor, Azman; Mohd Yunus, Saidatolakma (Brill Academic Publisher, 2014)
The build, operate and transfer (BOT) contract has widely been applied in developing economies since the participation of private sectors has declined in the reconstruction and funding of public infrastructure. BOT is a financing and operating approach, which has been practiced primarily in the area of infrastructure privatization in developing countries. Recently, application of the BOT scheme has been carried out in many waqf institutions, especially Majlis Agama Islam Wilayah Persekutuan. The BOT approach offers new perspectives in the field of waqf as it has the capability to enhance waqfproperty for the public’s benefit. Property enhancement is the major reason why waqf is enjoined by Islam. Waq f institutional involvement in developing its property and public infrastructures by way of BOT contracts is proving to be a challenging exercise. This article examines the current practice of applying BOT contracts in waq f institutions in general and in Majlis Agama Islam Wilayah Persekutuan in particular, with specific reference to the application of other types of contracts. In addition, the practice is discussed in terms of its compliance with the principles of Sharīʿah law. Moreover, this article aims to identify the issues, problems as well as challenges that might face waqf institutions during implementation of BOT contracts.